ADEQUATE APPROACH TO THE DIAGNOSIS AND SURGICAL TREATMENT OF PATIENTS WITH OSTEOPORTIC FRACTURES OF THE VERTEBRAL BODIES - Alikhodjaeva, G.A.; Alimov, I.R.; Kazakov, Sh. J. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Vertebral fractures due to osteoporosis are a significant medical and socio-economic problem. Puncture vertebroplasty is an effective type of treatment for vertebral fractures and relief of pain associated with osteoporosis. Adequate conservative treatment of osteoporosis in the postoperative period slows down the progression of this disease and reduces the likelihood of new fractures of the spine in the complex treatment of this disease.